Risk Factors Of Stunting In Children Aged 12-59 Months In The Working Area Of The Langara Puskesmas District, Konawe Islands, 2022 - Wulan, Martri; Salma, Wa Ode; Sudayasa, I Putu (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2023)
Background: Stunting is a global health problem because it increases the risk of morbidity and mortality in children. Indonesia is the third largest country in Southeast Asia with the number of cases (21.6%), while the Konawe Islands Regency (32.2%). Objective: To analyze the factors that influence the incidence of stunting in toddlers in the working area of the Langara Public Health Center, Konawe Islands Regency. Methods: This study used a case-control study design with a total sample of 112 respondents consisting of 56 cases and 56 controls. Samples were taken using simple random sampling technique, where control cases have the same right to be respondents. Measuring tools used to measure stunting are the Infantometer/Length board and microtoise, chronic energy deficiency is measured using maternal and child health books, while social status is measured using a questionnaire that has been tested for validity and reliability. The results of variable measurements were then analyzed using the odds ratio test. Results: history of maternal chronic energy deficiency (p = 0.013; OR = 3.316; 95% CI = 1.256-8.750), socioeconomic (p = 0.007; OR = 2.885; 95% CI = 1.319-6.307). Conclusion: chronic energy shortages, and socio-economic risk of stunting in toddlers in the work area of the Langara Public Health Center, Konawe District, Islands